1998
DOI: 10.1002/(sici)1097-4628(19981024)70:4<717::aid-app11>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative polymerization of phenylenediamines by enzyme and magnetic properties of the products

Abstract: Oxidative polymerization of m-phenylenediamine was carried out using H 2 O 2 as an oxidant and horseradish peroxidase as a catalyst in mixtures of aqueous buffer solution and 1,4-dioxane or in reversed micellar solutions. When the reaction mixture was brought into contact with a stainless steel stick, the obtained polymer responded to a permanent magnet at room temperature in the air. From the ICP emission spectroscopic analysis, it was found that these polymers contained small amounts of transition metals, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…It is reported that HRP can catalyze the oxidative polymerization of aromatic amines, phenol, and their derivatives. 71 Reversed micellar systems were also applicable to HRP-catalyzed polymerization of PD. 73 A typical polymerization procedure in a homogeneous system is as follows: A solution of PD and HRP in a mixture of 1,4-dioxane, phosphate, and 4-(2-hydroxyethyl)-1-piper-azineethanesulfonic acid (HEPES) buffer solution was first prepared.…”
Section: A Enzyme-catalyzed Oxidative Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that HRP can catalyze the oxidative polymerization of aromatic amines, phenol, and their derivatives. 71 Reversed micellar systems were also applicable to HRP-catalyzed polymerization of PD. 73 A typical polymerization procedure in a homogeneous system is as follows: A solution of PD and HRP in a mixture of 1,4-dioxane, phosphate, and 4-(2-hydroxyethyl)-1-piper-azineethanesulfonic acid (HEPES) buffer solution was first prepared.…”
Section: A Enzyme-catalyzed Oxidative Polymerizationmentioning
confidence: 99%
“…16,18,19,22,25,37,45,47,49,50,53 There are extensive studies in the literature concerning the synthesis, characterization, and application of conductive polymers of this family. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Thus far, various nitrogenous polymers of the family have been prepared by different methods, as shown in Table 1. PAN has been successfully prepared by several techniques including chemically oxidative polymerization, 7,75 electrochemically oxidative polymerization, 76,77 plasma polymerization, 78 and photoinduced electron-transfer photooxidative polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…An absorption band at 495 nm was observed with a shoulder band at 468 nm with increasing absorbance and the growth was complete in 100 s. The oxidative polymerization of o-phenylenediamine in the Nafion film was initiated by HAuCl 4 and led to the formation of Au@PoPD nanocomposite materials. The absorption band at 468 nm is attributed to the p-p ⁄ transition associated with the phenazine unit and 495 nm is due to the p-p ⁄ transition of the quinoneimine units [36,37]. Thus the chemical oxidative polymerization of o-phenylenediamine to PoPD formation was confirmed.…”
Section: Resultsmentioning
confidence: 76%
“…The formation of a large number of quinoid units in the backbone of PoPD is observed at the lower pH whereas the higher pH yields a large number of benzenoid units in the backbone of the PoPD [27,39]. The peak observed at 1530 cm À1 is due to the benzenoid ring stretching and the other peak at 1620 cm À1 is due to the quinoid ring stretching vibration of the PoPD [37]. The ratio of the spectral intensities of the 1530 cm À1 (benzenoid) and 1620 cm À1 (quinoid) peaks indirectly provides the protonation level of the PoPD polymer [39].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation